2019
DOI: 10.4049/jimmunol.1900395
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin Interacting Protein 1 Maintains Metabolic Homeostasis during B Cell Development by Modulating AMPK, mTORC1, and TFE3

Abstract: Folliculin interacting protein 1 (Fnip1) is a cytoplasmic protein originally discovered through its interaction with the master metabolic sensor 59 AMP-activated protein kinase (AMPK) and Folliculin, a protein mutated in individuals with Birt-Hogg-Dubé Syndrome. In response to low energy, AMPK stimulates catabolic pathways such as autophagy to enhance energy production while inhibiting anabolic pathways regulated by the mechanistic target of rapamycin complex 1 (mTORC1). We previously found that constitutive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…We hypothesized that human FNIP1 deficiency may hamper B-cell metabolism similar to Fnip1-deficient mice [2][3][4][5][6][7][8] . Indeed, circulating P1 B-cells exhibited increased numbers of mitochondria and mitochondrial activity relative to healthy control (HC) B-cells ( Figure 1F and supplemental Figure 9).…”
Section: Fnip1 Deficiency Is Associated With Altered Cell Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that human FNIP1 deficiency may hamper B-cell metabolism similar to Fnip1-deficient mice [2][3][4][5][6][7][8] . Indeed, circulating P1 B-cells exhibited increased numbers of mitochondria and mitochondrial activity relative to healthy control (HC) B-cells ( Figure 1F and supplemental Figure 9).…”
Section: Fnip1 Deficiency Is Associated With Altered Cell Metabolismmentioning
confidence: 99%
“…Mouse Fnip1 consists of 1,165 amino acids and shares 91% amino acid identity with human FNIP1 5 . Fnip1 plays a nonredundant role in early B-cell development and metabolism, skeletal muscle fiber type specification, and cardiac function [2][3][4][5][6][7][8] . Our report confirms that the clinical and immunological phenotypes are strikingly overlapping (i.e., HCM, pre-excitation syndrome, and early and severe B-cell defect with agammaglobulinemia).…”
Section: Fnip1 Deficiency Is Associated With Altered Cell Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Folliculin interacting protein 1 (FNIP1) is an adaptor protein originally identified through its interaction with folliculin (FLCN) and AMPK [18]. Previous studies have implicated that FNIP1 influences cellular metabolic regulators such as AMPK and mTOR signaling [19][20][21][22][23]. However, the exact roles of FNIP1 in modulating AMPK or mTOR signaling remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Whole body deletion of Fnip1 in mice has recently been shown to increase type I muscle fiber composition and activate AMPK signaling [20], whereas it has also been shown that mice with loss of FNIP1 in muscle actually have reduced phosphorylation of the catalytic α subunit of AMPK (Thr172) [21]. Similarly, both suppression and activation of mTOR signaling by FNIP1 have also been reported [20,21,23,24]. Collectively, the results of previous studies suggest a role for FNIP1 in muscle fiber type specification and metabolism.…”
Section: Introductionmentioning
confidence: 99%